Carneous mole in a depressed patient: a diagnostic dilemma - Bhagat, Nisha; Raj, Rajnish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Carneous mole is a pathological variant of missed abortion of a fetus less than 12 weeks. It’s medically managed by giving repeated doses of misoprostol with or without dilatation and curettage. Due to ambiguity in diagnosis and misleading clinical examination and investigations, surgical exploration was considered as the best approach. The case of carneous mole with depression is reported because of its rarity; as in this case, ammenorrhea was the only presenting complaint and all other laboratory tests, investigations and radiological report failed to detect carneous mole, which was diagnosed incidentally on exploratory laparotomy.